Analisis Inovasi Produk UMKM Agribisnis (Tanaman Hias)dengan Pendekatan Ekonomi Islam terhadap Peningkatan Daya Saing Lokal (Studi Kasus Kota Bandung) - Salam, Mochamad Fadlani; Siregar, Muhammad Zaki Mulia; Rahayu, Sinta Sri; Fadhillah, Ilham; Nurfauziah, Muhammad Adistya (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
This study examines product innovation in ornamental plant agribusiness MSMEs in Bandung City using an Islamic economics approach to enhance local competitiveness. The method used is qualitative descriptive, combining in-depth interviews with three MSMEs and a review of previous research literature. Findings indicate that integrating the principles of honesty, fairness, and trustworthiness into every stage of innovation, from the use of decorated used pots to the development of "Islamic Cacti," to Islamic decoration packages, builds trust perception and customer loyalty. Family and community collaboration, along with educational-spiritual storytelling, strengthens product differentiation in the local market. The resulting "Islamic Values-Based Product Innovation" model modifies the sharia marketing mix by adding elements of religious narrative as a driver of competitive advantage. Practical implications include the development of an integrated innovation module with Islamic values for MSMEs, government support policies, and quantitative measurement of the impact of Islamic economics-based innovation.